The Future of Creation Order Vol. 2, Order Among Humans: Humanities, Social Science and Normative Practices (New Approaches to the Scientific Study of Religion ,, 2018)
This book investigates humanities, social sciences and politics from the perspective of the concept of creation order. It is the second volume in a series that provides a unique and topical overview of attempts to assess the current health of the concept of creation order within Reformational philosophy when it is compared with other perspectives. Divided into a section on fundamental reflections and a section on normative practices, it discusses issues such as redemption, beauty, nature, love, justice, morality, and ethics. It concludes with discussions on a practice-based theory to explain religion in international relations and a normative model for the practice of cooperation in development. This series reflects the role that the branch of Christian philosophy called 'Reformational' philosophy plays in the discussion on the status of laws of nature. Ever since its inception, almost a century ago, the concepts of order and law (principle, structure) have been at the heart of this philosophy. One way to characterise this tradition is as a philosophy of creation order. Firmly rejecting both scholastic metaphysics and Deism, Reformational philosophers have maintained the notion of law as 'holding' for reality. Questions have arisen about the nature of such law: is it a religious or philosophical concept; does law just mean 'orderliness'? How does it relate to laws of nature? Have they always existed or do they 'emerge' during the process of evolution?